The CORRELATION BETWEEN PARENTING STYLES AND SMARTPHONE ADDICTION AMONG PRIMARY SCHOOL STUDENTS IN INDONESIA - Astrida Budiarti; Dya Sustrami; Vivi Febriani (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Introduction: Long term usage of smart phones will influence the physical and psychological conditions of children. Parents need to supervise the use of smart phones to overcome the impact of playing smart phones. The purpose of this study was to determine correlation of parenting styles with children's smart phone addiction rates in Indonesia. Materials and Methods: The design of the study used correlative analytics with a cross-sectional approach. The population was elementary school students at grades four, five, and six on Islamic elementary school in Indonesia. The Proportionate stratified random sampling technique was applied to get the sample and got 70 students as the respondents. The data were collected by using the Parenteral Authority Questionnaire (PAQ) and Smartphone Addiction Questionnaire. Data analysis using the Chi-Square test. Results: Most students had parents with a democratic parenting style (48.6%), and most students experienced moderate addiction (54.3%). The chi-Square test shows a relationship between parenting with smart phone addiction and the results of ρ = 0.042. Conclusion: This study indicated that proper parenting style could reduce the incidence of smart phone addiction, so parents need to applied effective parenting. For the school to always provide direction and guidance in the form of socialization to students about the effects of excessive smart phone use. The nursing profession, especially the local community health centers, is expected to be able to collaborate with schools to minimize the incidence of smartphone addiction by providing socialization about the impact of smartphone use.